2022
DOI: 10.1111/joes.12506
|View full text |Cite
|
Sign up to set email alerts
|

Reputational risks in banks: A review of research themes, frameworks, methods, and future research directions

Abstract: This study examined the research trends on reputational risk in banks using a systematic literature review and network analysis (SLRNA) approach on 35 research articles published between 2010 and 2020. It was found that only developed countries (i.e., the United States and Europe) have been actively contributing to research on reputational risks in banks, suggesting that reputational risks management of banks has not gained the global attention it deserves. Moreover, we identified five broad research themes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…This finding is in line with that of Suh and Han [102], who reported that authentication and confidentiality play a major role in the perceptions of app reliability in the context of e-commerce. To build a sense of confidence and reliability in consumers, it is also important to include comprehensive and accessible privacy and security policies [103]. Given the above, we hypothesise that: H4.…”
Section: Reliabilitymentioning
confidence: 99%
“…This finding is in line with that of Suh and Han [102], who reported that authentication and confidentiality play a major role in the perceptions of app reliability in the context of e-commerce. To build a sense of confidence and reliability in consumers, it is also important to include comprehensive and accessible privacy and security policies [103]. Given the above, we hypothesise that: H4.…”
Section: Reliabilitymentioning
confidence: 99%
“…It provides a systematic overview of the information described in publications in a statistical way that supports the analysis of tendencies and themes of a given area of research (Watrianthos et al, 2023) (Samala, Usmeldi, Taali, Ambiyar et al, 2023). Such techniques provide systematic insights by describing statistical information in publications, allowing the examination of trends and themes in each area of research (Adeabah et al, 2023). There are four stages of research in bibliometric analysis (Samala, Usmeldi, Taali, Daineko, et al, 2023), which are illustrated in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of such an effect was evidenced for the US banks during the global financial crisis: banks were sceptical of accessing the Fed discount window because if it became known, it might be interpreted as a signal of weakness (Armentier et al , 2015). This impact would also likely differ for recapitalised and non-recapitalised banks, given the possibility of some kind of reputation risk associated with the former (Fiordelisi et al , 2013; Barakat et al , 2018; Brei et al , 2020; Adeabah et al , 2022). Taking these considerations on board, we estimate the baseline specification for all banks and separately by their recapitalisation status.…”
Section: Robustness Checksmentioning
confidence: 99%